(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The main aim of the article is to analyze a specific type of tourism, which is dark tourism, also known as thanatotourism or dark tourism. The phenomenon of dark tourism is characterized here, its types are specified and selected places are described, examples of the thanatotourism product: Chernobyl, The Suicide Forest in Japan, 9/11 Memorial dedicated to the victims of the attack on the WTC, tourist offer related to the Titanic disaster, Museum of War Remnants in Vietnam. Attention was paid to the motives of visitors to such places and the fact that not every visit to a facility associated with human suffering, tragedy or death is a manifestation of thanatotourism.